KESANTUNAN BERBAHASA MAKASSAR DI KELAS VI UPT SD NEGERI 16 TAMALATEA KABUPATEN JENEPONTO - Wahyuni, Sri Putri; Daeng , Kembong; Asri, Aswati (Journal Studies in Indonesian Language and Literature, 2024)
This study aims to (1) describe the form of politeness compliance in Makassar language in learning interaction, (2) describe the form of politeness violation in Makassar language in learning interaction. This research is a qualitative research with descriptive design. Data collection techniques in this research used observation method, free listening technique and recording technique. Data analysis in the study used qualitative descriptive analysis method, namely (1) data tabulation, (2) data presentation, (3) interpretation, and (4) making conclusions. The results showed that there is (1). The form of politeness compliance in Makassar language in learning interaction is in the form of (a) maxim of wisdom, (b) maxim of praise, (c) maxim of agreement, and (d) maxim of sympathy. (2). The form of violation of politeness in Makassar language in the interaction is in the form of (a) maxim of wisdom, (b) maxim of praise, (c) maxim of agreement, and (d) maxim of sympathy.